Instructors' Efforts In Empowering Trainees Through Innovative Learning Methods - Cahyani, Anggun Mega; Ishaq, Muhammad; Ahmad, Ahmad (Universitas Negeri Malang, 2024)
This study aims to explore the efforts of instructors in empowering trainees through innovative learning methods at the Technical Implementation Unit of the Wonojati Vocational Training Center (UPT BLK) in Malang. The innovative learning methods applied include ice breaking, rewards, and participatory expository approaches. Instructors at UPT BLK Wonojati actively design and implement these methods by understanding the context and needs of the trainees. The research findings indicate that the innovative learning methods applied successfully enhanced the trainees' motivation, participation, and learning outcomes. Ice breaking created a conducive and enjoyable learning atmosphere, while rewards provided additional encouragement for trainees to excel. The participatory expository method helped trainees better understand the material through active interaction. In conclusion, the efforts of instructors in using innovative learning methods at UPT BLK Wonojati have had a positive impact on the learning process and outcomes. This study recommends the continued use and further development of innovative learning methods to improve the quality of training and the empowerment of trainees. Keywords: innovative learning methods, ice breaking, rewards, expository, UPT BLK Wonojati, trainee empowerment.